Hospital contextual factors affecting the use of health technologies: a systematic review. (13th November 2019) - Grossi, A; Hoxhaj, I; Gabutti, I; Carini, E; Pezzullo, A M; Cacciatore, P; Specchia, M L; Cicchetti, A; Boccia, S; de Waure, C
Abstract: Background: Healthcare systems are facing great challenges due to increased share of aging population, growing health needs and economic restraints. To keep a high quality of assistance it is important to invest in health technologies (HTs) that have the potential of improving health outcomes. Even though a lot of guidance does exist on how HTs should be introduced, used and dismissed, there is a surprising gap in literature concerning the awareness of hospitals in the actual utilization of HTs, namely utilization in daily practice after formal adoption. Methods: We performed a systematic literature review of qualitative and quantitative studies aimed at investigating hospital contextual factors that influence the actual utilization of HTs at hospital level. PubMed, Scopus, Web of Science, Econlit and Ovid were searched to retrieve studies published in English from 1st January 2010 to 31st May 2018. Results: A total of 33 studies were included mostly addressing information and communication technologies (ICTs). Findings suggest that contextual factors that impact on actual utilization of HTs at hospital level are ascribable to four main families: financial factors, leadership styles, human resource management and hospital infrastructure. It emerges also that involving professionals at all levels and planning people's work and competencies are major determinants of HTs actual utilization. Conclusions: The evidence suggests that several contextual factors play a major role in HTs actual utilization at hospital level even though data are mostly referred to ICTs being the other HTs unexplored. Indeed, findings from this study suggest that numerous items should be evaluated when considering to use a new HTs at hospital level. Nevertheless, evidence regarding actual utilization of medical and surgical HTs is still lacking and future research is needed. Key messages: Financial factors, leadership styles, human resource management, hospital infrastructure are relevant determinants of actual utilization of new HTs at hospital level. The evidence on contextual factors that influence actual utilization of HTs is mostly referred to ICTs and further research is indeed deserved.